2014
DOI: 10.1007/s13197-014-1412-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of pomegranate juice and whey based novel beverage fermented by kefir grains

Abstract: Mixture of pomegranate juice and whey was evaluated as a potential substrate for production of a novel probiotic beverage by kefir grains. Different fermentation conditions were used as viz: two fermentation temperature (19ºC and 25ºC) and two levels of kefir grains inoculum (5 % and 8%w/v). pH, acidity, lactose consumption as well as organic acids formation were determined during 32 hours of fermentation. Results showed that kefir grains were able to utilize lactose and decrease pH, increase acidity, produce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 16 publications
(24 reference statements)
3
23
1
1
Order By: Relevance
“…This might be duo to the optimum temperature for enzymes or metabolic activities of microorganisms in kefir grains. Also, it was observed that different fermentation conditions resulted in difference at pH (Sabokbar and Khodaiyan 2014). Therefore, this difference is another reason for these results, knowing that optimum pH influences the liberation of enzymes derived from the microorganisms (Boskov-Hansen et al 2002).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This might be duo to the optimum temperature for enzymes or metabolic activities of microorganisms in kefir grains. Also, it was observed that different fermentation conditions resulted in difference at pH (Sabokbar and Khodaiyan 2014). Therefore, this difference is another reason for these results, knowing that optimum pH influences the liberation of enzymes derived from the microorganisms (Boskov-Hansen et al 2002).…”
Section: Resultsmentioning
confidence: 97%
“…Also changes of total phenolic content and antioxidant activity during fermentation will be examined. In previous study (Sabokbar and Khodaiyan 2014) apple juice was used and good results were obtained for sensory evaluation and antioxidant activities. Therefore in present study pomegranate will be used because first examined showed mixture of pomegranate juice and whey would be have good sensory properties such as color and taste.…”
Section: Highlightmentioning
confidence: 99%
“…The value was significantly higher than that produced by L. acidophilus (4.9 g/L) and L. paracasei (4.46 g/L), whereas L. delbruekii only yielded 5.3 g/L lactic acid. Around 4.6 to 5.9 g/L of lactic acid was also produced by fermenting a mixture of P. granatum juice and whey in the study of Sabokbar and Khodaiyan (). In the present study, L. casei was able to produce 5.5 g/L lactic acid at 37°C after being fermented with the whole fruit‐squeezed P. granatum juice.…”
Section: Resultsmentioning
confidence: 99%
“…This drink is fermented with kefir grains, which are symbiotic associations of bacteria and yeast in which proteins and polysaccharides are also present. Sabokbar and Khodaiyan (2014) developed a drink composed of whey and apple juice fermented by kefir grains and studied the optimal incubation temperature and the grain quantity able to release the higher amount of phenolic content and antioxidant activity. It has been established that some peptides obtained by hydrolysis of the whey proteins ALA and BLG have antioxidant activity; in addition, apples contain many kinds of polyphenol components.…”
Section: Fermented Drinksmentioning
confidence: 99%